2001
DOI: 10.1096/fj.00-0383com
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR3gene structure, regulatory region, and sequence polymorphisms

Abstract: Vascular endothelial growth factor receptor 3 (VEGFR-3) is required for cardiovascular development during embryogenesis. In adults, this receptor is expressed in lymphatic endothelial cells, and mutant VEGFR3 alleles have been implicated in human hereditary lymphedema. To better understand the basis of its specific endothelial lineage-restricted expression, we have characterized the VEGFR3 gene and its regulatory 5' flanking region. The human gene contains 31 exons, of which exons 30a and 30b are alternatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…The 5′UTR of the human VEGFR-3 gene contains multiple repetitive elements, making it difficult to amplify by PCR (ref. 28 and data not shown). Thus we chose primers that flank 3 CSL binding sites (-3818, -3687, and -3456) outside of the repetitive elements to amplify the precipitated DNA.…”
Section: Notch Upregulates Vegfr-3 In Primary Human Endothelial Cellsmentioning
confidence: 76%
See 2 more Smart Citations
“…The 5′UTR of the human VEGFR-3 gene contains multiple repetitive elements, making it difficult to amplify by PCR (ref. 28 and data not shown). Thus we chose primers that flank 3 CSL binding sites (-3818, -3687, and -3456) outside of the repetitive elements to amplify the precipitated DNA.…”
Section: Notch Upregulates Vegfr-3 In Primary Human Endothelial Cellsmentioning
confidence: 76%
“…It has been suggested that the endothelial expression of VEGFR-3 is regulated at both the transcript and protein levels (28,29), yet little is known about these regulatory mechanisms. The portion of VEGFR-3 promoter that specifically drives expression of VEGFR-3 in BECs and LECs has been previously described (28). We identified 3 CSL consensus sequences (-747, -574, and -565) in this same VEGFR-3 regulatory region (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the Vegfr3 intron͞ exon boundaries, we aligned the Vegfr3 cDNA sequence (Accession no. L07296) with the VEGFR3 genomic sequence (17), and amplified exons 16 through 26 of Vegfr3, which were then sequenced from the C3H, B6, BALB͞c, BbxD2, and PES strains. We used the K14-VEGF-C156S and Vegfr3 ϩ/Ϫ mice in the crosses (10,12).…”
Section: Methodsmentioning
confidence: 99%
“…Vascular endothelial growth factor receptor 3 (VEGFR-3), which is associated with angiogenesis, is a receptor tyrosine kinase that is expressed in lymphatic endothelial cells (Iljin et al, 2001). Binding of VEGFR-3 to the ligands VEGF-C or VEGF-D stimulate lymphangiogenesis (Alitalo & Carmeliet, 2002), while in carcinogenesis, the production of VEGFs by tumors promote metastases and result in decreased survival (Su et al, 2006).…”
Section: Elevated Vascular Endothelial Growth Factor Receptor 3 (Vegfmentioning
confidence: 99%